Overtides, compound tides, and tidal-residual current in Ensenada de la Paz lagoon, Baja California Sur, Mexico - Juan A. Delgado; Juan A. Dworak; José Gómez-Valdés (Geofísica Internacional, 2003)
Nonlinear tidal interactions in the shallow coastal lagoon Ensenada de la Paz, Mexico are investigated using a vertically-integrated two-dimensional numerical model. The model is calibrated with observations of sea surface elevation and currents. Two runs are implemented to study the role played by different bottom friction parameters. A dominant momentum balance between the pressure gradient force and the frictional force is found. MK3, SK3, MS4, and M4 were the most energetic shallow water tides. They are mainly generated by a quadratic bottom friction law. A coherent tide-induced residual current was found. Two anticyclonic eddies were generated at the inlet, they were correlated to the M4 tidal energy flux. In the lagoon, in the deeper region, an anticyclonic eddy was generated, which was correlated with the M2 and K1 energy fluxes; but in the shallower region, a cyclonic eddy was generated, which was correlated with the M4 energy flux.